A: PENGARUH PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG - Istikhomah, Siti; Srimindarti, Ceacilia (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Investors have their own choices for investing capital, one of which is considered by looking at the accuracy of reporting financial statements. This test is conducted to assess the factors that are considered to have an impact on audit report lag. Examining factors from the use of independent variables, namely provability, solvency, and company size, while the independent variable is audit report lag. In this study, the population was taken from manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2018-2022. The use of purposive sampling technique in determining the sample. Secondary data was used as the data source in this study, which was conducted using a quantitative research approach. Multiple linear regression analysis was used as a data analysis method, which was carried out using software from SPSS. Based on the results, it was found that profitability and solvency had no effect. However, the results of company size influence the audit report lag negatively. Keywords : Audit report lag, Profitability, Solvency, Company size, Manufacturing